2015
DOI: 10.1097/lgt.0000000000000136
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smartphones as Adjuvant Tools for Cervical Cancer Screening in Low-Resource Settings

Abstract: Smartphone images may be a useful adjunct to conventional VIA and VILI for the detection of CIN2+ and improve cervical cancer screening in low-resource settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 12 publications
0
61
0
Order By: Relevance
“…An example of effective low-cost leveraging of mobile technologies comes from work in Ambanja, Madagascar, where smartphones were used to take and transmit high-definition images for the detection of cervical intraepithelial neoplasia of grade 2 or worse as an adjunct to standard on-site examination. 82 …”
Section: Using Social Media and Mhealth Apps In Low-resource Settingsmentioning
confidence: 99%
“…An example of effective low-cost leveraging of mobile technologies comes from work in Ambanja, Madagascar, where smartphones were used to take and transmit high-definition images for the detection of cervical intraepithelial neoplasia of grade 2 or worse as an adjunct to standard on-site examination. 82 …”
Section: Using Social Media and Mhealth Apps In Low-resource Settingsmentioning
confidence: 99%
“…While not specific to cervical cancer screening, previous studies have found a positive association between telemedicine and increased access to specialized care, decreased costs to patient, reduced treatment costs at earlier stage of disease, and overall increased socioeconomic returns [ 7 ]. With increasing access to internet and mobile phone connectivity, telemedicine offers potential solutions for improving access and quality of cervical screening for women in low-resource settings as well as those who have reduced access to screening services due to geographical station [ 8 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study conducted in Madagascar has shown that off-site detection of cervical lesions based on the evaluation of smartphone photographs was more reliable than on-site diagnosis alone [5]. The aim of this study was to assess the clinical performance of D-VIA and D-VILI examinations for diagnosing cervical lesions in LMICs.…”
Section: Introductionmentioning
confidence: 99%